Model of Monitoring and Evaluation of Character Education at Universitas PGRI Semarang - Sumardiyani, Listyaning; Reffiane, Fine; Ayu, Ngurah; Lestari, Siti (International Journal of Active Learning, 2017)
Universitas PGRI Semarang has integrated character education into the fabric of its academic and non-academic activities. It has consciously set about creating a moral climate within universitys fourth pillar of Catur Dharma/ Modeling. Dynamic monitoring and evaluation system for character education is impetus in order to adequately meet the demands of recommended core values: personal and social awareness, self-management, and social skill.Though its slogan and core values are in the domain of character education, its monitoring, evaluation, and assessment have not integrated one and another yet.Thus, it is pertinent to conduct a research for desiging an effective model of monitoring and evaluation of character education.The study used three stages of R & D research method: desiging, revising,and field testing. Expert validation scores had gained 83.35 % while professional validation was 84.5%. It means the model both theoretically and practically is appropriate for evaluation of characters education. The results indicated that to be fully effective and ongoing of the program, integrated monitoring, measuring, and assessing system should be in conjunction with monitoring evaluation design, its implementation as well as its instruments. The study recommends the university and other institutions have to transfer this conceptual model into an implementation model in which character education functions harmonically and in a coordinated manner to provide effective and efficient results.